Assessing the techno-economic benefits of LEMs for different grid topologies and prosumer shares - Markus Doepfert; Soner Candas; Hermann Kraus; Peter Tzscheutschler; Thomas Hamacher (iScience)
Summary: The shift toward decentralized and renewable energy sources has introduced significant challenges to traditional power systems, necessitating innovative market designs. Local energy markets present a viable solution for integrating distributed energy resources such as photovoltaic systems, electric vehicles, and heat pumps. This study investigates the techno-economic implications of local energy markets compared to conventional market designs, focusing on their impact on average energy prices and operational peak power. Through comprehensive simulations across various grid topologies with varying penetration levels of the distributed energy resources, totaling 400 simulation setups, we demonstrate that local energy markets can enhance economic efficiency and grid stability with 99% of the scenarios boasting lower average energy prices and 80% lower operational peak power levels. The findings suggest that local energy markets can play a role in the future energy system, provided that additional infrastructure, management costs, and bureaucratic complexity are kept to a minimum.